A ‘Liberal’ Revolution? 1688 as Sattelzeit - Vallance,Edward (2022)
Abstract This paper reflects on the nature of the English revolution of 1688, examining the way in which the revolution has tended to be presented as a temporal marker. While the notion of the revolution as the founding moment in the establishment of a liberal political order has largely been abandoned, the idea of 1688 as a historical watershed has proved persistent. Recent historical interpretations oscillate between seeing the revolution as representing the end of earlier historical processes (the reformation, the mid-century revolution) and seeing it as the beginning of modernity. The 1696 Association to William III has been identified by scholars such as Steven Pincus and Mark Knights as revealing the modernizing effect of the revolution. This article examines the same moment, employing Reinhart Kosseleck’s notion of Sattelzeit to instead argue for 1688 as a transitionary period in which multiple senses of time and historical change co-existed.